Interação silício e alumínio em plantas de arroz de terras altas e mamona - Freitas, Lucas Barbosa de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aluminum toxicity is a major limiting productivity in acid soils and Si is an interesting way to minimize the Al3+ toxicity in plants, however, the mechanism of this interaction between Si and Al3+ is not well understood. The objectives underlying this work were: evaluate the efficiency of aluminum sources and doses in causing toxicity in upland rice plants grown in nutrient solution; describe the susceptibility to Al3+ by upland rice cultivars currently used by Brazilians farmers; describe the susceptibility of castor bean cultivars of FCA - UNESP' plant breeding program; evaluate the interaction between Si and Al3+ in upland rice plants (Si-accumulator plant) and castor bean (non-Si-accumulator plant). Were installed five greenhouse experiments, conducted in nutrient solution. All experiments were laid out in randomized block design, with four replications. Experiment 1 - arranged in factorial design 2x4, the treatments were two Al3+ source (aluminum sulfate and aluminum chloride) and five Al3+ doses (0; 370; 740; 1100 and 1480 μmol L-1) evaluated in upland rice plants. Experiment 2 - arranged in factorial design 2x9, the treatments were with and without Al3+ and nine upland rice cultivars. Experiment 3 - arranged in factorial design 2x9, the treatments were with and without Al3+ and nine castor bean cultivars. Experiment 4 - arranged in factorial design 2x4, the treatments were two upland rice cultivars (Maravilha Al3+ susceptible and ANa 7007 Al3+ tolerant) and four Si e Al3+ combinations (1-without Si and without Al3+; 2-with Si and without Al3+; 3- without Si and with Al3+, 4-with Si and with Al3+). Experiment 5 - arranged in factorial design 2x4, the treatments were two castor bean cultivars (CRZ H18 Al3+ susceptible and CRZ H06 Al3+ tolerant) and four Si e Al3+ combinations (1-without Si and without Al3+; 2-with Si and without Al3+; 3- without Si and with Al3+, 4-with Si and with Al3+) ...

A toxicidade ao alumínio (Al3+) é um dos principais limitantes da produtividade em solos ácidos e o silício (Si) é uma forma interessante de se minimizar a toxidez por Al3+ em plantas, porém, ainda não se conhece de forma clara o mecanismo envolvido na interação Si e Al3+. Assim, os objetivos que fundamentaram esse trabalho foram: avaliar a capacidade de fontes e doses de Al3+ em causar toxidez em plantas de arroz de terras altas cultivadas em solução nutritiva; avaliar a suscetibilidade ao Al3+ de cultivares de arroz de terras altas utilizados atualmente por agricultores brasileiros; avaliar a suscetibilidade ao Al3+ de linhagens de mamona do programa de melhoramento genético da FCA - UNESP; avaliar a interação Si e Al3+ em plantas de arroz de terras altas (cultura acumuladora de Si) e mamona (cultura não acumuladora de Si). Foram instalados cinco experimentos em casa de vegetação, conduzidos em solução nutritiva. Todos utilizaram delineamento em blocos casualizados e quatro repetições. Experimento 1 - disposto em modelo fatorial 2x5, os tratamentos foram duas fontes de Al3+ (sulfato de alumínio e potássio e cloreto de alumínio) e cinco doses de Al3+ (0; 370; 740; 1100 e 1480 μmol L-1) avaliadas em plantas de arroz de terras altas. Experimento 2 - disposto em modelo fatorial 2x9, os tratamentos foram com e sem Al3+ e nove cultivares de arroz de terras altas. Experimento 3 - disposto em modelo fatorial 2x9, os tratamentos foram com e sem Al3+ e nove linhagens de mamona. Experimento 4 - disposto em modelo fatorial 2x4, os tratamentos foram dois cultivares de arroz de terras altas (ANa 7007 - tolerante e Maravilha - suscetível ao Al3+) e quatro combinações de Si e Al3+ (1 – sem Si e sem Al3+; 2 – com Si e sem Al3+; 3 – sem Si e com Al3+; 4 – com Si e com Al3+). Experimento 5 - disposto em modelo fatorial 2x4, os tratamentos foram duas linhagens de mamona ...
Interaction silicon and aluminum in upland rice and castor oil plants
Keywords: Arroz - Cultivo; Plantas - Efeito do aluminio; Fenóis; Plantas - Efeito do silício; Plants, Effect of aluminum on